Socialization of Anti-Hoax Strategy for the Success of the 2024 Election in Desa Kesiman Petilan - Indrawati, Sri; Made Chandra Mandira, I (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2024)
General elections have become a worldwide phenomenon, where elections are the best way to ensure a peaceful transition of power because elections are a big national party that includes all people who have been registered as permanent voters, during the preparation period there are often hoax news about campaigns. This is because people still cannot distinguish what is true and what is not. The purpose of this community service is to try to invite all generations to help provide Anti-Hoax Strategy Socialization in the success of the 2024 Kesiman Petilan Village Election. The method used is an active participation method, especially socialization, socialization is a communication process carried out with active participation from two parties. This socialization provides an understanding to the people of Kesiman Petilan Village about the importance of conducting elections and reminds people to be more careful in using social media so as not to easily believe in hoax news. The results and conclusions of this socialization have made the public more aware of news spread on social media whose truth is not yet known, and the public has also become more participating in the 2024 election activities.